2016
DOI: 10.1103/physrevlett.117.127401
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Transition from Lasing Driven by a Bosonic to a Fermionic Reservoir in a GaAs Quantum Well Microcavity

Abstract: We show that by monitoring the free carrier reservoir in a GaAs-based quantum well microcavity under nonresonant pulsed optical pumping, lasing supported by a fermionic reservoir (photon lasing) can be distinguished from lasing supported by a reservoir of bosons (polariton lasing). Carrier densities are probed by measuring the photocurrent between lateral contacts deposited directly on the quantum wells of a microcavity that are partially exposed by wet chemical etching. We identify two clear thresholds in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Figure 2(a) shows the current as a function of the optical pump power, at constant voltage, for two different devices. Linear or sublinear dependence on the illumination power was observed in a very similar structure [20] when there was no extended polariton condensate in the ground state. We see sublinear behavior, as expected from the classical circuit model discussed in Appendix B, when we have a quasicondensate localized at the pump spot, e.g., as seen in the data of Device 1 at low power in Figure 2(a), where a clear saturation is seen.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Figure 2(a) shows the current as a function of the optical pump power, at constant voltage, for two different devices. Linear or sublinear dependence on the illumination power was observed in a very similar structure [20] when there was no extended polariton condensate in the ground state. We see sublinear behavior, as expected from the classical circuit model discussed in Appendix B, when we have a quasicondensate localized at the pump spot, e.g., as seen in the data of Device 1 at low power in Figure 2(a), where a clear saturation is seen.…”
Section: Resultsmentioning
confidence: 69%
“…[17][18][19], but in almost all cases with vertical injection; Ref. [20] also studied lateral injection, similar to our geometry, as discussed below.…”
mentioning
confidence: 86%
“…of polaritons may evolve into a standard semiconductor laser [19,20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…However, the GB is absent in most of the PL experiments [1,6,30,[32][33][34][35][36][41][42][43][44][45]. There are only a few exceptions that reported observation of GB, which are the experiments done in extremely high density regime [40] or in a strongly disordered system [49] where polaritons were forced to scatter into the GB.…”
Section: Introductionmentioning
confidence: 99%
“…Lagoudakis et al 9 showed exciton-polaritons can interact with carriers when free electrons and holes are introduced in the same in the same QW with the excitons or in a neighboring QW. Brodbeck et al 10 distinguished photon lasing from polariton lasing by monitoring the free carrier reservoir in a GaAs-based quantum well microcavity. It is expected to see some peculiar optical features when exciton-polaritons and free carriers are confined together.…”
Section: Introductionmentioning
confidence: 99%